(untitled) (The Pretoria Student Law Review, 2021)
Twenty years after the adoption of the Constitution, it is fitting to reflect on the development of our constitutional democracy. In light of purposive interpretation of statutes, one is required to question the intention of the drafters of the Constitution, to consider the context which necessitated its promulgation and to contemplate whether effect has been given to the content of the rights and freedoms contained therein. Ever-increasing inequalities in our society have prompted a return to the promise of ‘transformative constitutionalism’. Klare defines transformative constitutionalism as a ‘long-term project of constitutional enactment, interpretation, and enforcement’ committed to transforming political and social institutions ‘in a democratic, participatory, and egalitarian direction.’ The main problem which will be evaluated in this article is identified by Klare as the ‘formalistic legal culture’ which persists in all spheres of our socio-political and economic life.